2018
DOI: 10.1186/s12909-018-1274-3
|View full text |Cite
|
Sign up to set email alerts
|

Academic dishonesty among academics in Malaysia: a comparison between healthcare and non-healthcare academics

Abstract: BackgroundThis study was carried out to gauge the prevalence of academic dishonesty among academics in Malaysian universities. A direct comparison was made between academics of healthcare and non-healthcare courses to note the difference in the level of academic integrity between the two groups. In addition, the predisposing factors and implications of academic dishonesty, as well as the different measures perceived to be effective at curbing this problem were also investigated.MethodsA cross-sectional study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Recent study by Tiong, Kho, Mai, Lau, & Hasan (2018) revealed that academicians as respondents have personally encountered at least one case of academic dishonesty involving their peers; and the major factors found because of low level of self-discipline and integrity. The study also identify that the most common form of misconduct is absenteeism from work.…”
Section: Unethical Behaviour In Higher Learning Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study by Tiong, Kho, Mai, Lau, & Hasan (2018) revealed that academicians as respondents have personally encountered at least one case of academic dishonesty involving their peers; and the major factors found because of low level of self-discipline and integrity. The study also identify that the most common form of misconduct is absenteeism from work.…”
Section: Unethical Behaviour In Higher Learning Institutionsmentioning
confidence: 99%
“…Chapman 2014Embezzlement, misappropriation of funds, changing students grade for money or favours, selling admissions, selling examination scores or grade, falsifying data, gift authoring, ghost authoring Abanobi 2017Desperation for promotion, greed for money and lack of commitment to the profession Tiong, Kho, Mai, Lau, & Hasan (2018) absenteeism from work, giving of publication authorship to non-contributor, academic plagiarism, covering up of student's exam malpractice, falsification of research data/finding, taking adjunct lectureship without permission from the university, leaking of exam questions, forcing students to buy books or other learning materials, falsifying exam records, writing student assignments for money and accepting bribes to change student grades.…”
Section: Unethical Behaviour In Higher Learning Institutionsmentioning
confidence: 99%
“…They may also cause prospective physicians to be deprived of the necessary scientific knowledge, and deviate from one of the most important values of the medical profession, which is honesty [6]. Tiong et al revealed that there was a significantly higher prevalence of academic dishonesty among healthcare academics than among their peers who did not work in healthcare [12]. In research conducted in Coratia, only 9% of 198 sophomores stated that they never plagiarized at all [6].…”
Section: Introductionmentioning
confidence: 99%
“…Building on to our previous findings where academics' integrity and professionalism has an impact to students' skill and competency training, we were interested to determine whether CSL can replace didactic teaching, in order to increase the consistency in teaching by lecturer and to minimise human's errors. 16,17 Therefore, the purpose of this study was to evaluate and compare the effect of CSL and traditional lecture on knowledge, Deep Information Processing (DIP) and motivation among pharmacy students.…”
Section: Introductionmentioning
confidence: 99%